Strengthening the Role of Alumni in Improving the Quality and Quantity of Students - Rahmawati Alwi; Fawaid, Milahtul Latifah; Baharun, Tafriza Imam Amrullah (Al-Qalam Institue, 2025)
This research examines the role of alums in enhancing both the quality and quantity of students at pesantren. The study aims to identify the contributions of alumnae, as well as the supporting and inhibiting factors, and the impact of alumnae involvement on pesantren development. Using Participatory Action Research (PAR), the study involved alums, administrators, and students in collaborative activities. The findings revealed that alums are crucial in mentoring, skill development, and promoting the pesantren. Their active participation significantly increases student enrollment, with the majority of new students joining through alum referrals. However, challenges such as poor coordination, communication issues, and geographical obstacles were identified among alums. The study concludes that strengthening alum engagement is crucial to enhancing both the quality and quantity of students. It recommends that the pesantren improve alumni communication through digital platforms and establish more structured alum programs. This research contributes to understanding alum networks in Islamic educational institutions and suggests further exploration into the use of digital tools and sustainable alum programs.